Pancreas-Protocol Imaging at a High-Volume Center Leads to Improved Preoperative Staging of Pancreatic Ductal Adenocarcinoma - Walters, Dustin M. (2011)
BACKGROUND: High-quality preoperative cross-sectional imaging is vital to accurately stage patients with pancreatic ductal adenocarcinoma (PDAC). We hypothesized that imaging performed at a high-volume pancreatic cancer center with pancreatic imaging protocols more accurately stages patients compared with pre-referral imaging. METHODS: We retrospectively reviewed data from all patients with PDAC who presented to the surgical oncology clinic at our institution between June 2005 and August 2009. Detailed preoperative imaging, staging, and operative data were collected for each patient. RESULTS: A total of 230 patients with PDAC were identified, of which 169 had pre-referral imaging. Patients were selectively reimaged at our institution based on the quality and timing of imaging at the outside facility: 108 (47%) patients were deemed resectable, 54 (23.5%) were deemed borderline-resectable, and 68 (29.5%) were deemed unresectable. Of the resectable patients, 99 opted for resection. Eighty-two of those 99 patients underwent preoperative imaging at our institution, and of these 27% had unresectable disease at the time of surgery compared with 47% of patients who only had pre-referral imaging (p = 0.14). Reimaging altered staging and changed management in 56% of patients. Among that group were 55 patients, categorized as resectable on pre-referral imaging, who on repeat imaging were deemed to be borderline resectable (n = 27) or unresectable (n = 28). CONCLUSIONS: Pancreas-protocol imaging at a high-volume center improves preoperative staging and alters management in a significant proportion of patients with PDAC who undergo pre-referral imaging. Thus, repeat imaging with pancreas protocols and dedicated radiologists is justified at high-volume centers.